Rohingya-The Stateless Community Becoming the Lost Generation - Mahbubur RAHMAN; Haradhan Kumar MOHAJAN (Journal of Economic Development, Environment and People, 2019)
The Rohingya is a Muslim ethnic minority group in Rakhine State of Myanmar.It is now established but controversial fact that the Rohingya is a stateless population of the world who has found shelter across vast swathes of Asia mainly in Bangladesh, and also in India, Pakistan, Thailand and Malaysia. But a majority of Rohingyas are living in various camps of Bangladesh with statelessness identity. Recently, the UN warns that the Rohingya children who are living in various camps of Bangladesh would be the lost generations of the world. This article discusses the aspects of “stateless community” and “lost generation” of the world’s most persecuted people-the Rohingya.